Ethnic Chinese Networks in International Trade - Rauch, James E.; Trindade, Vitor (The Review of Economics and Statistics, 2002)
We find that ethnic Chinese networks, proxied by the product of ethnic Chinese population shares, increased bilateral trade more for differentiated than for homogeneous products. This suggests that business and social networks have a considerable quantitative impact on international trade by helping to match buyers and sellers in characteristics space, in addition to their effect through enforcement of community sanctions that deter opportunistic behavior. For trade between countries with ethnic Chinese population shares at the levels prevailing in Southeast Asia, the smallest estimated average increase in bilateral trade in differentiated products attributable to ethnic Chinese networks is nearly 60%.